Telemedicine and Medical Education in the Age of COVID-19. (December 2020) - Jumreornvong, Oranicha; Yang, Emmy; Race, Jasmine; Appel, Jacob
Abstract : The COVID-19 pandemic has offered medical schools an opportunity to incorporate telemedicine training into the curricula in a timely and practical manner. Telemedicine has grown exponentially in the United States, and the shift toward remote care to align with social distancing guidelines is fueling this growth. Training medical students to deliver high-quality, secure, and personalized health care through telemedicine will prepare the next generation of physicians to conscientiously use these technologies and meet a growing need for telehealth services. Telemedicine-specific educational goals can be incorporated into curricula and integrated with existing clinical experiences to provide students with core telemedicine and clinical skills to prepare them for current and future pandemics. Medical educators could explore 5 major telemedicine domains: (1) access to care, (2) cost, (3) cost-effectiveness, (4) patient experience, and (5) clinician experience. Schools could use the following learning vehicles to help medical students explore these domains: (1) asynchronous lectures covering telehealth history; (2) discussions on applications, ethics, safety, etiquette, and patient considerations; (3) faculty-supervised standardized patient telehealth encounters; and (4) hands-on diagnostic or therapeutic procedures using telehealth equipment. Incorporating telemedicine into the medical school curriculum exposes students to the application of telemedicine across specialties as well as its limitations.